Assessment Practices of Mathematics Teachers in Oman (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Mathematic teachers’ assessment practices can be concluded as essential practices of mathematicsteachers toward achieving the aims of teaching mathematics. This research aimed to determine the teachers’ assessment practices of mathematical thinking in Oman. A total of 245 mathematics teachers (134 females and 111 males), who teach at public schools in Oman, participated in this research. A scale of assessment practices of mathematical thinking was used to record the responses of the teachers. The results of the research showed that the teachers used several assessment practices to assess students’ mathematical thinking. The formative assessment practices were used more than the other assessment practices, and the least used was electronic assessment practices. The findings of this study provide practical implications for mathematic teachers in Oman.